PENINGKATAN KAPASITAS SOFT SKILL REGULASI DIRI MELALUI PELATIHAN BAGI KARYAWAN DI PERUSAHAAN “XYZ” - Wibowo, Doddy Hendro; Raharja, Kho Susan; Paijanto, Yohanes (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
Abstract: Human resources that are well managed will provide roles in an effective and efficient manner for the company. Companies need to improve the quality of human resources in facing challenges. One of the soft skills that need to be developed and improved is the ability in self-regulation for employees. The objectives of this activity are: to improve employees' self-regulation skills. Participants in this activity were 27 employees in the A department of XYZ Company. The employee development program consists of three stages, namely: a) the assessment stage; b) the training and development stage and; 3) the evaluation stage. Based on the development activities, it was concluded that there was an increase in employee self-regulation skills. Employees get learning and sharing skills between employees and department leaders, get role models and motivation, and employees can reflect on being able to be used adaptively in their work. Key words: Self-regulation skills, training, human resources